A bilingual advantage in 54‐month‐olds' use of referential cues in fast mapping. Issue 1 (23rd November 2016) - Yow, W. Quin; Li, Xiaoqian; Lam, Sarah; Gliga, Teodora; Chong, Yap Seng; Kwek, Kenneth; Broekman, Birit F.P.
Abstract: Research has demonstrated a bilingual advantage in how young children use referential cues such as eye gaze and pointing gesture to locate an object or to categorize objects. This study investigated the use of referential cues (i.e. eye gaze) in fast mapping in three groups of children that differed in their language exposure. One hundred and seven 54‐month‐old children who were English monolinguals ( n  =   28), English‐Mandarin bilinguals ( n  =   48), and English‐Mandarin bilinguals with exposure to a third language (i.e. trilinguals, n  =   31) were assessed with a word learning task using two types of test – a referent test and a mutual exclusivity test. During the task, following the gaze of an adult speaker was needed to be able to indicate the correct referent of a novel word at test. All three groups of children demonstrated successful word learning in explicit selection of and implicit looking time toward the target object during testing. However, bilingual and trilingual children outperformed their monolingual peers in both types of test when they were asked to explicitly select the correct objects. These findings suggest positive effects of bilingualism on children's use of referential cues in fast mapping. Abstract : This research investigated the use of referential cues (i.e., eye gaze) in fast mapping in three groups of children with different linguistic experience (monolingual, bilingual, and trilingual). Bilingual and trilingual children outperformed their monolingual peers during the test phase when asked to explicitly select the target referent. Multilingual children's heightened sensitivity to others' referential intent extends to fast mapping of words in a social context.